Use of Facebook as a Tool for Knowledge Dissemination in Dermatology. Issue 5 (September 2014) - Kim, Whan; Vender, Ronald
Background: The presence of dermatology-related platforms in social media has been acknowledged; however, the level of engagement of the public with these platforms has not been evaluated. Objective: To use the Engagement Rate to assess the level of engagement of the public with Facebook pages devoted to dermatology. Methods: A search on Facebook identified Facebook pages for dermatology academic journals, professional societies, and patient-centered groups with the highest number of Facebook likes. Then the Yearly Page Engagement Rate was calculated for each Facebook page. Results: The robust average of the Yearly Page Engagement Rate was 0.673 for academic journals, 0.313 for professional societies, and 1.563 for patient-centered groups. Conclusion: Patient-centered groups engaged with their fans most effectively. Engagement is a key determinant of a fan's exposure to the contents of the page and hence a gauge of whether the fans who "liked" the page continue to remain engaged or not.